COVID-19 Vaccine-Associated Immune Thrombosis and Thrombocytopenia (VITT): Diagnostic Discrepancies and Global Implications - Zidan, Ali; Noureldin, Abdelrahman; Kumar, Shreya Anil; Elsebaie, Abdelrahman; Othman, Maha (Seminars in Thrombosis and Hemostasis, 2023)
Vaccine-induced immune thrombotic thrombocytopenia (VITT) has been reported in association with the coronavirus disease 2019 preventative adenovirus vector-based vaccines ChAdOx1 nCoV-19 (Oxford/AstraZeneca) and Ad26.COV2.S (Janssen/Johnson & Johnson) in hundreds of recipients across the globe. VITT is characterized by thrombosis, typically at unusual sites, low fibrinogen, and elevated plasma D-dimer, generally manifesting between 4 and 28 days following vaccination. Detection of anti-platelet factor antibodies using an enzyme-linked immunosorbent assay (ELISA) is often confirmatory. Although several similar principles subside in most diagnostic criteria for VITT, the presentation of a positive ELISA assay, use of expert hematology and neurology opinion, and exclusion of possible VITT cases outside the “standard” 4 to 28-day timeframe have contributed a lack of global standardization for defining VITT. Accordingly, the global and regional incidence of VITT differs according to the diagnostic pathway and case definition used. This has influenced the public perception of VITT's severity and the decision to use adenovirus vector-based vaccines for limiting severe acute respiratory syndrome coronavirus 2 infection. We hereby delineate the recognized pathogenic mechanisms, global incidence, discrepancies in diagnostic criteria, recommended treatments, and global implications to vaccine hesitancy from this coagulopathy.
Keywords: VITT; COVID-19; SARS-CoV-2; adenoviral vector vaccines